ANALYSIS GROUND SURFACE SPECTRA ACCELELERATION ON CENTRAL JAKARTA REGION USING NERA - HANDAYANI (NIM : 25006027) Pembimbing : Ir. Bigman Marihat Hutapea, M.Sc, Ph.D., AULIA
Earthquake loading on the buildings is based on earthquake motions to groud surface through free field medium. This research conducted to analysis ground surface spectra acceleration for free field condition using software NERA which based on time domain. Nine cases condition that vary depth of baserock (100 ft, 165 ft and 230 ft) and three mekanism (benioff, megathrust dan shallow crustall) . The results are described on spectra acceleration diagram and in ground surface spectra envelope formed based on UBC 1997. The results of spectra are compared with flushp output from the last research (Imanuel Mangape, 2009). The results are showed that spectra acceleration on free filed condition from flushp is bigger than NERA output, except on 2.0 seconds period. The results of spectra acceleration envelope are also compared with Indonesian Standard Building Code (SNI 2003) and also with International Building Code (IBC 1996). The results are showed that NERA spectra acceleration envelopes are slightly less than SNI 2003 and IBC 1996